TATHBȊQ WASȊLAH AL-TA'LIM "POWTOON" FȊ TARQIYYATI MAHᾹRAH AL-‎QIRᾹ'AH‎ - Hanifah, Umi; Hidayah, Muhfidatul Winda Winda (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Among the problems of learning Arabic in Islamic schools is the number of students who find it difficult to learn reading skills, one of the reasons is the use of learning media that is not effective and causes students to get bored. Therefore, in this study the authors examine the "Powtoon" learning media to improve reading skills. The purpose of this study was to determine the application of the "Powtoon" learning media and the effectiveness of its application in improving reading skills, therefore this research is very important for Arabic teachers in solving the problem of learning reading skills. This study is a quantitative study. The subjects in this study were students of class VII at State Islamic Junior High School 2 Sidoarjo. Data collection uses observation, interview and test. The results showed that the application of the "Powtoon" learning media was effective in improving the reading skills students of class VII at State Islamic Junior High School 2 Sidoarjo with a score of t_0, the result was 29.8 and tt was 1.701, so t_0 was greater than tt which means that the null hypothesis (Ho) is Rejected and the alternative hypothesis (Ha) is accepted. Keywords: Learning Media, Powtoon, Reading Skills,